2022
DOI: 10.3390/microorganisms10061243
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantum Infection of Primary Human Myeloid Cells

Abstract: Circulating phagocytic cells often serve as cellular targets for a large number of pathogens such as Leishmania parasites. Studying primary human cells in an infectious context requires lengthy procedures for cell isolation that may affect the analysis performed. Using whole blood and a no-lyse and no-wash flow cytometric assay (NoNo assay), we monitored the Leishmania infantum infection of primary human cells. We demonstrated, using fluorescent parasites, that among monocyte cell populations, L. infantum pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The Leishmania spp. are obligate intracellular parasites that reside in phagocytic cells, including macrophages, neutrophils, monocytes, and dendritic cells, during this chronic infection [ 24 , 25 ]. The presence of intracellular parasites alters the phenotype and function of infected host phagocytes [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Leishmania spp. are obligate intracellular parasites that reside in phagocytic cells, including macrophages, neutrophils, monocytes, and dendritic cells, during this chronic infection [ 24 , 25 ]. The presence of intracellular parasites alters the phenotype and function of infected host phagocytes [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both CanL and HWD are potentially zoonotic parasitoses. L. infantum is a causative agent of visceral leishmaniasis in humans with clinical manifestations of fever, anemia, weight loss, splenomegaly, hepatomegaly, and even death, if left untreated; however, a large number of cases may be asymptomatic [3]. Humans are not specific hosts for D. immitis to develop to the adult stage.…”
Section: Discussionmentioning
confidence: 99%
“…Amastigotes (the aflagellate form of the parasite) live and multiply within macrophages and other cells of the reticuloendothelial system of mammals as vertebrate hosts. Dogs are the main reservoir of L. infantum; however other species can be infected, such as cats [1], ferrets [2], and humans [3]. Livestock (sheep, goats, cattle, and donkeys) reared in outbreak areas [4], as well as wildlife [5], can be important sources of human leishmaniasis.…”
Section: Introductionmentioning
confidence: 99%
“…The special edition has also provided new advances for a better understanding of host- Leishmania interactions with Picard et al, describing new approaches for a better comprehension of infection [ 9 ]. The work showcased by Picard et al presented the NoNo flow-cytometric approach as a possible new tool for understanding the interactions between Leishmania and the host [ 9 ].…”
mentioning
confidence: 99%
“…The special edition has also provided new advances for a better understanding of host- Leishmania interactions with Picard et al, describing new approaches for a better comprehension of infection [ 9 ]. The work showcased by Picard et al presented the NoNo flow-cytometric approach as a possible new tool for understanding the interactions between Leishmania and the host [ 9 ]. With fluorescent parasites, these authors demonstrated that among primary human monocyte populations in whole blood, L. infantum preferentially infects classical (CD14+ CD16−) and intermediate (CD14+ CD16+) populations.…”
mentioning
confidence: 99%